2023
DOI: 10.1136/bmjqs-2022-015725
|View full text |Cite
|
Sign up to set email alerts
|

Physician engagement in organisational patient safety through the implementation of a Medical Safety Huddle initiative: a qualitative study

Abstract: BackgroundEfforts to increase physician engagement in quality and safety are most often approached from an organisational or administrative perspective. Given hospital-based physicians’ strong professional identification, physician-led strategies may offer a novel strategic approach to enhancing physician engagement. It remains unclear what role medical leadership can play in leading programmes to enhance physician engagement. In this study, we explore physicians’ experience of participating in a Medical Safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Evidence-based IRS best practices include having clear roles and responsibilities for events, greater engagement from clinicians of diverse professions and fostering of shared experiences from reports with visible action. 18 Publicly rewarding high-impact reports, 19 fostering physician-specific spaces for discussion of safety concerns 20 and involving managerial non-clinician staff 21 can increase engagement. Most research to date focuses on hospital-wide IRSs, but a greater understanding of the complementary role of physician-specific and specialty-specific IRS is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based IRS best practices include having clear roles and responsibilities for events, greater engagement from clinicians of diverse professions and fostering of shared experiences from reports with visible action. 18 Publicly rewarding high-impact reports, 19 fostering physician-specific spaces for discussion of safety concerns 20 and involving managerial non-clinician staff 21 can increase engagement. Most research to date focuses on hospital-wide IRSs, but a greater understanding of the complementary role of physician-specific and specialty-specific IRS is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of BMJ Quality & Safety, Rotteau et al 8 describe their qualitative study on medical safety huddles implemented at six sites. In contrast with organisation-led, multidisciplinary huddles, these huddles included only physicians.…”
mentioning
confidence: 99%
“…And although traditional multidisciplinary huddles are designed as safe spaces for raising safety and performance concerns, Rotteau et al found that physician-specific huddles enabled discussions of 'safety concerns that were specifically related to physicians' clinical roles, especially when contrasted with 'nursing' concerns that are typically discussed in the local unit level huddles'. 8 In other words, medical safety huddles create an opportunity for physicians to share role-specific concerns that they would otherwise be hesitant to raise in a broader group.…”
mentioning
confidence: 99%